Glycaemic Status in Different Stages CKD Patients by CKD EPI Formula due to Diabetic Nephropathy - Fatema, Naznin; Khurshid, Tazrian; Afrooz, Farhana; Syed Md Rashedul Hasan, Abu; Taufique Reshma, Samira; Mohajan, Monisha; Asgar Chowdhury, Nabil (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Diabetes is one of the important causes of Chronic Kidney Disease (CKD) in both developed and developing countries. Around one third of diabetic patients develop CKD. Controlling hyperglycaemia may halt the progression of diabetic kidney disease patients to ESRD (End Stage Renal Disease). Worlwide, more than 140 million people suffer from diabetes, making this one of the most common noncommunicablediseases. The aim of the study to find out the glycaemic status of diabetic nephropathy in different stages of CKD. Materials and methods: This is a cross sectional study. This study was done Medicine and Nephrology Department of CMCH over 100 patients during the period June to December 2014. Staging of CKD in this patient will be done by CKD- EPI formula and Glycaemic status was evaluated by fasting and 2HABF and HbA1C. Sociodemographic data was compared. Staging of Diabetic Nephropathy (DN) was evaluated by either urinary Albumin Creatinine Ratio (ACR) or Urinary Total Protein (UTP). Results: Among 100 patients studied regarding sex most of them are male (60%). .Regarding occupational status most of them were engaged in business (33%) and house wife (36%). Average (71%) socioeconomic status commonly foundand most of them were doing moderate works (80%) and most patients were from rural (74%) origin. Dip stick test was found positive among (55%) cases. Fundal examination findings revealed preproliferative retinopathy was commonest (49%). Stage 5 CKD was found in 35% cases rest were at stage 3 and 4. In ultrasonogram study Illdefined corticomedullary differentiation was found in 68% cases. Highest creatinine was found 12.3 and HbA1c was found 13. Relation of CKD stages with Fasting blood sugar (p= 0.473), blood sugar 2 hours after breakfast (p=0.312), HbA1c (p=0.120) were found insignificant and relation with eGFR was found highly significant (p=0.001). Conclusions: This study defined a scenario of Glycaemic status of CKD patients admitted in a tertiary care hospital. No significant relation of Glycaemic status were found with different stages of CKD in our setting. Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 6-9